2016
DOI: 10.1002/nau.23050
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of mirabegron and imidafenacin in women with overactive bladder: A randomized crossover study (the MICRO study)

Abstract: Mirabegron and imidafenacin have the same efficacy. Imidafenacin administration is associated with a higher rate of dry mouth, blurred vision, and constipation as compared to mirabegron administration. Neurourol. Urodynam. 36:1097-1103, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(50 reference statements)
1
11
1
Order By: Relevance
“…These data were better than the persistence rate with antimuscarinics in previous reports. 11 The differences in tolerability with these two types of medication could greatly influence the continuation of medication. Combination therapy with antimuscarinics and mirabegron could be a better treatment option for female patients' satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were better than the persistence rate with antimuscarinics in previous reports. 11 The differences in tolerability with these two types of medication could greatly influence the continuation of medication. Combination therapy with antimuscarinics and mirabegron could be a better treatment option for female patients' satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…8 A recent randomized cross-over study also showed that mirabegron had the same efficacy and a lower rate of dry mouth, blurred vision and constipation compared with an antimuscarinic agent imidafenacin. 11 The differences in tolerability with these two types of medication could greatly influence the continuation of medication.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy and safety of MIRA has been proved in several phase III clinical trials . Additional studies have shown that MIRA appears to be as effective as antimuscarinics and shows a lower incidence of drug‐related TEAEs . One‐year persistence rates of up to 66.0% have been reported, with improved persistence and adherence versus antimuscarinic therapy …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Additional studies have shown that MIRA appears to be as effective as antimuscarinics and shows a lower incidence of drug-related TEAEs. 8,9 One-year persistence rates of up to 66.0% have been reported, with improved persistence and adherence versus antimuscarinic therapy. 10,11 International urological associations recommend MIRA and antimuscarinics for treating patients with OAB symptoms.…”
mentioning
confidence: 99%
“…There is accumulating evidence that mirabegron has about the same degree of effectiveness as a standard antimuscarinic [30,31] and that combination therapy with an antimuscarinic can produce improved control of symptoms [32]. Concerns about cardiovascular toxicity have largely proven to be unfounded [33].…”
Section: Second Line: Pharmacologicalmentioning
confidence: 99%